Research and development of control system for semi-automatic infirm wheelchair mobility using head motion - Phun-apai, Nittalin; Limboonruang, Teerapath (International Journal of Engineering and Technology, 2019)
The objective of this research is to improve and develop the control system for semi-automatic infirm wheelchair mobility using a head motion for the disabled person wheelchair to fulfill the need of the person with the disability of arms and legs as the result of accident or illness as the result of an underlying disease. The disabled person can control this disabled person wheelchair by the use of head via semi-automatic infirm wheelchair mobility control unit using a head motion for wheelchair mobility. The wheelchair comprises of 2 sets of DC motor (24 V 450 W) and 2 sets of battery (12 V 45 Amp), which are connected for manipulation in driving forward and moving to the left or right side. Brake system is applied to the safety of the disabled person and can be controlled the wheelchair mobility by use of the head to press a switch. The finding of the testing result indicated maximum average velocity of forwarding mobility in horizontal mobility (going forward) at 3.97 kilometers/hour, maximum slope ascending mobility of 15 degrees at average ascending mobility velocity of 2.41 kilometers/hour, minimum left turning circle at 1.54 meters, minimum right turning circle at 1.60 meters, minimum braking distance at 0.49 meters, andÂ 7-hour usability of battery duration per one charging (charging duration took around 3 hours/time). The finding from the tests conducted with the disabled persons indicated that it could be well used by disabled people without dependence and more convenient for daily life.Â